2021
DOI: 10.1177/11782218211046261
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and Perspectives From Women Taking Investigational Therapy for Hepatitis C Virus During Pregnancy

Abstract: Objective: Describe the experiences and perspectives among pregnant people with chronic HCV infection receiving ledipasvir/sofosbuvir (LDV/SOF) therapy during pregnancy. Methods: We conducted semi-structured, in-depth interviews within an open-label, phase 1 study of LDV/SOF therapy among pregnant people with chronic HCV infection. Participants took 12 weeks of LDV/SOF and were interviewed at enrollment and again at the end of treatment. We transcribed the interviews verbatim and coded them with NVivo software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…This positive perspective has been noted in other studies [24,25]. In work by Kislovskiy et al, interviews of nine pregnant people who were enrolled in an open-label, phase 1 study of ledipasvir/sofosbuvir during pregnancy yielded themes related to treatment during pregnancy being tolerable and convenient; taking DAAs increased individuals' sense of well-being due to the possibility of cure; and participants appreciated the provision of non-judgmental, person-centered care and communication [23]. Although Kislovskiy et al's study was conducted among individuals who had already agreed to enroll in an early stage trial, it is reassuring that these individuals similarly identified a cure from HCV as "life changing" and were very positive about antepartum treatment [23].…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…This positive perspective has been noted in other studies [24,25]. In work by Kislovskiy et al, interviews of nine pregnant people who were enrolled in an open-label, phase 1 study of ledipasvir/sofosbuvir during pregnancy yielded themes related to treatment during pregnancy being tolerable and convenient; taking DAAs increased individuals' sense of well-being due to the possibility of cure; and participants appreciated the provision of non-judgmental, person-centered care and communication [23]. Although Kislovskiy et al's study was conducted among individuals who had already agreed to enroll in an early stage trial, it is reassuring that these individuals similarly identified a cure from HCV as "life changing" and were very positive about antepartum treatment [23].…”
Section: Discussionsupporting
confidence: 55%
“…Kushner et al surveyed patients and identified a high willingness to take DAA therapy during pregnancy if it would result in prevention of perinatal transmission; factors associated with receptivity to treatment included being of reproductive age range and having a prior history of HCV treatment [24]. These attitudes were echoed by pregnant participants in a phase 1 DAA trial [23]. In qualitative work exploring DAA implementation in the primary care setting, prescribing providers in Delaware expressed positive attitudes regarding HCV treatment, while also identifying patient-and practice-level barriers [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Access to well tolerated HCV treatment during pregnancy to achieve cure and prevent vertical transmission is appealing to women with HCV infection [105,106]. Combined with universal screening in pregnancy, DAA treatment during pregnancy could prove a potent mechanism for achieving HCV elimination in women and children, and we believe it should be a high priority for further study.…”
Section: Direct-acting Antiviral Treatment For Prevention Of Paediatr...mentioning
confidence: 99%